Synthesis and characterization of nanostructured TiO2-SnO2 composite - Breve, Joelma Cristina de Souza [UNESP]; Santos, Dayse Iara dos [UNESP] (Trans Tech Publications Ltd, 2014)
Nanostructured composites based on titanium dioxide have been studied in order to improve optical and photo-catalytic properties, as well as their performance in gas sensors. In this work, titanium and tin dioxides were simultaneously synthesized by the polyol method resulting in TiO2 platelet coated with SnO2 nanoparticles as was observed by scanning electron microscopy. The thermal analysis showed that the combined synthesis promotes more easily the crystallization of the TiO2 rutile phase. The composite obtained after heat treatment at 500 degrees C showed to be formed of almost only rutile phases of both oxides. The optical properties analyzed by UV-Vis spectroscopy showed that the combined oxides have higher absorbance, which reinforces a model found in the literature based on the flow of photo-generated electrons to the conduction band of SnO2 delaying the recombination of charges.
Keywords: Semiconductors nanocomposite; Polyol method; Titanium dioxide; Tin dioxide; Nanostructured materials; TiO2-SnO2 composite